Ocorrência de Braga cigarra (Cymothoidae) parasitando Galeocharax knerii (Characidae) de afluentes da represa de Jurumirim, Brasil - Brandão, Heleno [UNESP]; Toledo, Gislayne de Melo [UNESP]; Wunderlich, Alison Carlos [UNESP]; Ramos, Igor Paiva [UNESP]; Carvalho, Edmir Daniel [UNESP]; da Silva, Reinaldo Jose [UNESP] (FapUNIFESP (SciELO), 2013)
The occurrence of the cymothoidae Braga cigarra is reported parasitizing the oral cavity of freshwater fish Galeocharax knerii from Veados, Paranapanema and Taquari Rivers, affluent of the Jurumirim Reservoir, State of Sao Paulo, Brazil is reported. The isopod species were identified based on the multilaminar pleopods, narrow pleon and short pleotelson in females. The overall prevalences of isopods were 31.7%, 7.7% and 5.7%, respectively, in the Paranapanema, Veados and Taquari Rivers. This note contributes to the knowledge of the geographical distribution and fauna of parasite crustaceans known to date in these important ecosystems.
Occurrence of Braga cigarra (Cymothoidae) parasitizing Galeocharax knerii (Characidae) from affluents of Jurumirim reservoir, Brazil
Keywords: Braga cigarra; Crustacean parasite; Freshwater rivers; Galeocharax knerii; Teleost fish